2004
DOI: 10.1002/jemt.20089
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of MmM5/Mg multi‐layer hydrogen storage films prepared by magnetron sputtering

Abstract: KEY WORDStransmission electron microscopy; hydrogen storage alloys; thin films; magnetron sputtering ABSTRACT Multi-layer hydrogen storage thin films with Mg and MmNi 3.5 (CoAlMn) 1.5 (here Mm denotes La-rich mischmetal) as alternative layers were prepared by direct current magnetron sputtering. Transmission electron microscopy investigation shows that the microstructure of the MmNi 3.5 (CoAlMn) 1.5 and Mg layers are significantly different although their deposition conditions are the same. The MmNi 3.5 (CoAlM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Previous researches have demonstrated that the nanocrystalline MgNi thin film fabricated by direct current magnetron sputtering exhibited better kinetic performances than the usual polycrystalline phases, for which the hydrogen absorption and desorption temperatures decreased as reported before [19]. Previous studies also show that the thin MmM 5 layer acts as a catalyst to accelerate the hydrogenation/dehydrogenation process of the MgNi layer in MgNi/MmM 5 multilayer films [18]. Here, the presence of a uniform Pd layer catalyst, typically in form of nanoclusters on the MgNi surface, stimulates the surface reaction leading to the dissociation and recombination of the H 2 molecules and accelerates the hydrogenation/dehydrogenation process of the MgNi layer.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Previous researches have demonstrated that the nanocrystalline MgNi thin film fabricated by direct current magnetron sputtering exhibited better kinetic performances than the usual polycrystalline phases, for which the hydrogen absorption and desorption temperatures decreased as reported before [19]. Previous studies also show that the thin MmM 5 layer acts as a catalyst to accelerate the hydrogenation/dehydrogenation process of the MgNi layer in MgNi/MmM 5 multilayer films [18]. Here, the presence of a uniform Pd layer catalyst, typically in form of nanoclusters on the MgNi surface, stimulates the surface reaction leading to the dissociation and recombination of the H 2 molecules and accelerates the hydrogenation/dehydrogenation process of the MgNi layer.…”
mentioning
confidence: 72%
“…It was reported, for example, that Pd/Mg/Pd films can absorb and desorb hydrogen at 373 K and its hydrogen storage capacity reach the value as high as 5 mass% [17]. It has also been revealed that incorporation of LaNi 5 type alloys into Mg-base alloys by MA or sputtering can improve the hydriding kinetics of Mg-base alloys by an auto-catalysis reaction mechanism [2,18]. The reported work demonstrate obviously that good hydrogen storage performance (high hydrogen capacity and moderate absorption/desorption temperature) of Mg-base alloys can be achieved by forming nano-composite of Mg-base hydrogen storage alloys and proper catalyst [15][16][17][18].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…To improve the hydrogenation properties of Mg, Wang and Ouyang et al prepared Mg–Ni thin films, and Mg/MmM x and Mg-Ni/MmM 5 multi-layer films [69,70,71,72,73,74]. They prepared the Mg/MmM 5 multi-layer film via magnetron sputtering, and X-ray diffraction (XRD) analysis showed that most of the Mg was hydrogenated and dehydrogenated at about 523 K, which is about 100 K lower than the dehydrogenation temperature of pure Mg film.…”
Section: Strategies For Tuning the Thermodynamics Of Mg-based Alloysmentioning
confidence: 99%
“…Devi et al [2] found that the change in resistance for LaNi 5 thin film due to hydrogen absorption increases with the angle of deposition and resistance decreases with desorption. Recently, the microstructure of the Mg and MmNi 3.5 (CoAlMn) 1.5 multi-layered thin films was reported to be affected by the substrate temperature and the composition of the deposited layer [16]. Only limited reports were focused on the electrochemical hydrogen storage properties, no detailed analysis was associated to the microstructure of LaNi 5 based thin films.…”
Section: Introductionmentioning
confidence: 99%